The 5G Myth : When Vision Decoupled from Reality - Webb, William (De|G Press, 2018)
The 5G Myth explains why the vision of 5G, the next generation in mobile telephony, heralded as a huge advance in global connectivity, is flawed and sets out a better vision for a connected future. It explains why insufficient technological advances and inadequate profitability will be problems in the widespread implementation of 5G. The book advocates a focus on consistent connectivity everywhere rather than fast speeds in city centers. William Webb looks back at the transitions through previous generations of mobile telephony and shows what simple extrapolations of trends would predict for 5G. He discusses whether the increases in speed and capacity promised by 5G are needed; if the required technology is available; whether a sound business case can be made for the deployment; and asks why, given this, the industry appears so supportive of 5G. He then puts forth the argument in favor of consistent connectivity of around 10Mbits/s everywhere as a more compelling vision and shows how it can be delivered via a mix of 4G and Wi-Fi.